Bioelectrochemistry by fluorescent cyclic voltammetry - Mizzon, G (2012)
Understanding the factors influencing the ET characteristics of redox proteins confined at an electrochemical interface is of fundamental importance from both pure (fundamental science) and applied (biosensory) perspectives. This thesis reports on progress made in the emerging field of coupled electrochemical characterization and optical imaging in moving the analysis of redox-active films to molecular scales. More specifically the combination of cyclic voltammetry and wide-field Total Internal Reflection (TIRF) microscopy, here named ‘Fluorescent Cyclic Voltammetry’ (FCV), was applied to monitoring the response of surface-confined redox active proteins at submonolayer concentrations. The combined submicrometre spatial resolution and photon capture efficiency of an inverted TIRF configuration enabled the redox reactions of localized populations of proteins to be directly imaged at scales down to a few hundreds of molecules. This represents a 6-9 orders of magnitude enhancement in sensitivity with respect to classical current signals observed in bioelectrochemical analysis. Importantly, measurements of redox potentials at this scale could be achieved from both natural and artificially designed bioelectrochemical fluorescent switches and shed fundamental light on the thermodynamic and kinetic dispersion within a population of surface confined metalloproteins. The first three chapters of this thesis provide an overview of the relevant literature and a theoretical background to both the rapidly expanding fields of electroactive monolayers bioelectrochemistry and TIRF imaging. The initial design and construction of a robust electrochemically and optically addressable fluorescent switch, crucial to the applicability of FCV is reported in chapter 5. The generation of optically transparent, and chemically modifiable electrode surfaces suitable for FCV are also described. Chapter 6 describes the response of the surface confined azurin-based switch. Analysis of the spatially-resolved redox reaction of zeptomole samples in various conditions enables the mapping of thermodynamic dispersion across the sampled areas. In chapter 7 the newly developed FCV detection method was extended to investigate more complex bioelectrochemical systems containing multiple electron transferring redox centres and responding optically at different wavelengths. This approach provides a platform for spectral resolution of different electrochemical processes on the same sample. Finally in chapter 8 an electrochemical procedure is proposed for investigating the kinetic response of redox proteins using a fundamentally new methodology based on interfacial capacitance. In using variations in the surface chemistry to tune the rate of electron transfer, the approach was shown to be a robust and facile means of characterising redox active films in considerably more detail than possible through standard electrochemical methodologies. Ultimately, it can be applied to probe dispersion within protein populations and represents a powerful means of analysing molecular films more generally.